Millennials Green Culture: The Opportunity And Challenge (A Case Study Of Higher Education Student) - Ika Suhartanti Darmo (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Culture can be defined as a strong sense of an action, behavior, or way of thinking is understood to specific values; one of which is a green reduce, reuse, and recycle waste. Unfortunately, modernization, instant lifestyle, and lack of understanding or indoctrination of the family, the external environment and formal education institutions make the application of green with millennial Indonesia is relatively low. Millennial growing community that cared for in particular green waste management not only provide positive solutions for environmental management, but also the business and revenue opportunities candidate or beneficial to the family, the environment and local residents. The literature research is intended to sharpen the issue of the importance of the application of green culture in the millennial generation. The effectiveness of the application of green to the millennial culture requires active encouragement of formal educational institutions, companies and governments; thus providing a positive impact to inspire young people care more about the environment, and the rise of social-preneur generation participating improve the welfare of society.